Do-Not-Resuscitate (DNR) - Piryani, Rano Mal; Piryani, Suneel (Journal of Kathmandu Medical College, 2018)
Do-Not-Resuscitate (DNR) is well conceptualized, understood and implemented in developed countries in comparison to developing countries. DNR, DNAR (Do-Not-Attempt-Resuscitation), and AND (Allow-Natural-Death) are the same instructions or orders with an equal meaning. DNR is a therapeutic decision made before incident of cardiac or respiratory (cardiopulmonary) arrest with the consent of patient, or proxy consent of next of kin or authorized person if patient is not competent and sound. In this case, healthcare professionals provide no requisite CPR (Cardiopulmonary Resuscitation) without stopping any degree of normal care and therapy given to the patient. It is essential to consider who should discuss the DNR status and with whom, what and when it should be discussed, how should discussion be done and documented and who shall sign the DNR consent. Documentation in the patient’s medical record of a decision with regard to DNR and not to perform CPR must be incorporated both in clinician’s order and in the progress notes of the patient. The Nepal Medical Council’s guidelines for DNR are very clear and well spelt out but the implementation process is not documented. Healthcare decision must be taken on ethical ground besides clinical and technical ground. Healthcare professionals must be trained to become ethically competent. To effectively use and prevent misuse of DNR order, health professional must be educated about DNR.